A Group Interview regarding Disaster Preparedness for Food Assistance in a University that Offers a Training Course for Registered Dietitians. (January 2014) - Ito, Seira; Sudo, Noriko; Fujiwara, Yoko
Mass care feeding for disaster evacuees is an important component of public health preparedness. If universities that offer a training course for registered dietitians could provide food assistance to the evacuated people in their campus, it could contribute to maintain their health. Many universities are expected to become a base of support activities for people affected by disaster. This study aimed to reveal disaster preparedness in a university that offers a training course for registered dietitians, from the aspect of provision of mass care feeding. As Japan has 124 universities that offer such training courses, this case study could serve as a useful reference for them and contribute to the improvement of health of the affected people. A group interview was conducted in University A in 2012. The participants included two faculty members in the course, a vice president, a staff member, and a faculty member in charge of disaster preparedness and response. Stockpiled foods were limited to dry bread and pre-processed rice. No alternative heat sources were stored. It was concluded that to provide nutrients other than carbohydrate, hot meals should be served for the evacuees. Additionally, it would be difficult to provide meal service when the essential utilities such as gas and electricity are disrupted.